Doxorubicin-Loaded Fungal-Carboxymethyl Chitosan Functionalized Polydopamine Nanoparticles for Photothermal Cancer Therapy - Maduru Suneetha; Hyeonjin Kim; Sung Soo Han (MDPI AG, 2023)
In this work, we synthesized doxorubicin-loaded fungal-carboxymethyl chitosan (FC) functionalized polydopamine (Dox@FCPDA) nanoparticles for improved anticancer activity via photothermal drug release. The photothermal properties revealed that the FCPDA nanoparticles with a concentration of 400 µg/mL produced a temperature of about 61.1 °C at 2 W/cm2 laser illumination, which is more beneficial for cancer cells. Due to the hydrophilic FC biopolymer, the Dox was successfully encapsulated into FCPDA nanoparticles via electrostatic interactions and pi-pi stacking. The maximum drug loading and encapsulation efficiency were calculated to be 19.3% and 80.2%, respectively. The Dox@FCPDA nanoparticles exhibited improved anticancer activity on HePG2 cancer cells when exposed to an NIR laser (800 nm, 2 W/cm2). Furthermore, the Dox@FCPDA nanoparticles also improved cellular uptake with HepG2 cells. Therefore, functionalizing FC biopolymer with PDA nanoparticles is more beneficial for drug and photothermal dual therapeutic properties for cancer therapy.